(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the development and characterization of various invasome-loaded gel preparations containing Miconazole for the treatment of fungal infections. Six formulations (IG1 to IG6) were evaluated based on their physicochemical properties, pH, drug content, spreadability, viscosity, and cumulative drug release. Among the formulations, IG4 exhibited optimal characteristics, including the highest drug content (99.65±0.15%) and significant cumulative release (98.96±0.15% at 8 hours). The release kinetics followed Higuchi’s and Korsmeyers-Peppas models, indicating a diffusion-controlled release mechanism. Antifungal activity tests demonstrated that IG4 had comparable efficacy to Miconazole against Candida albicans, showing promising zones of inhibition. Stability studies confirmed that IG4 maintained its integrity and efficacy over time under varying storage conditions. Overall, IG4 represents a potential effective formulation for topical antifungal therapy, meriting further clinical evaluation.